Studi Keluhan Musculoskeletal Disorder (MSDs) di UD. Berkah Alam Tahun 2021 - Hanifah Dwi Lestari; Moch Sahri (VISIKES: Jurnal Kesehatan Masyarakat, 2021)
The rapid progress in the industrial sector has an important role in growing the economy. Without the industrial sector, growth in developing countries will be slower than in previous years. UD. Berkah Alam is one of the informal industrial sectors that focuses on coconut management. The types of jobs available at UD. The blessings of Nature are the pacak part, the scrap part, the daily part and the copra part. This type of work has a risk of musculoskeletal disorders. The study was conducted with the aim of knowing the prevalence of complaints of Musculoskeletal Disorders (MSDs) in each work section. The method used is a survey using a nordic body map using a questionnaire. The results showed that 59% of all workers experienced complaints of pain or pain, especially in the musculoskeletal system. Workers who experience complaints on the musculoskeletal system are highest in the copra (100%). Complaints of disorders experienced by workers of the right shoulder, left shoulder, buttocks, buttocks, right forearm and left forearm.